Good and evil and other stories - Schweblin, Samanta, 1978- (Alfred A. Knopf, 2025)
"Sculpted and lucid, strange and uncanny, here is a masterpiece of suggestiveness. Step by step these seven stories lure us into the shadows to confront the monsters of everyday life - ourselves. Guilt, grief, and relationships severed permeate this collection - but so do unspeakable bonds of family, love, and longing, each sinister and beautiful. When something seismic happens in our lives, the waves keep coming for years after, with warning or without. Sometimes, all we can do is wait around the corner, ear pressed to the phone receiver, for them to arrive. Fantastical and subtly terrifying, these stories draw on magical realism, psychological fiction, and the dark side of fairy tales, inherited from literary predecessors like the Brothers Grimm and Jorge Luis Borges. Yet, far from antiquated or closed off, Schweblin's worlds invite us in, like quicksand or a strong river's current. These stories will insinuate themselves into your heart, and your bloodstream"--